Evolution to emergence of green buildings: A review - Jam Shahzaib Khan; Rozana Zakaria; Siti Mazzuana Shamsudin; Nur Izie Adiana Abidin; Shaza Rina Sahamir; Darul Nafis Abbas; Eeydzah Aminudin (Administrative Sciences, 2019)
"Green Buildings" are essential in being responsive to the challenges of climate change and global warming while inhibiting natural resources degradation. This demand requires specific attention to increase the adoption of green-certified buildings within the construction industry. Innovative tools and techniques are needed to meet global challenges and strategies set for Sustainable Development Goals of 2030 agenda. This paper provides an intensive review of the evolution of green buildings from a sustainable development perspective which investigates the current global adoption of green buildings. Systematic Literature Review (SLR) and Selective Critical Literature Review Analysis (SCLRA) methodologies were adopted focusing on the content analysis to develop more in-depth knowledge. The scope of this study enlightens the sustainable development goals and initiatives. This paper highlighted that there is still inadequate adoption of green buildings and their rating tools on a significant basis in developing countries. This research adds a method towards the better understanding of green buildings and current scenarios that shall be considered for future research.
Keywords: 350; sustainability; sustainable development; green buildings; green building rating tools